Correcting the Misperceived Social Eating Norm to Dispel Pluralistic Ignorance and Increase Sustainable Food Choices - Reinoud Moojen; Marleen Gillebaart; Denise de Ridder (European Journal of Health Communication (EJHC))
Numerous factors influence people’s food choices, including the perceptions of eating habits of people in their immediate surroundings. Yet, these perceptions can be inaccurate, potentially leading people to misperceive the social eating norm and influencing them to make food choices that do not align with the actual social norm and their own true preferences. This phenomenon of misperception is called pluralistic ignorance. The current study’s primary goal is to examine whether misperceptions regarding sustainable eating can be corrected to promote sustainable food choices within a real-world food environment. To determine prevailing food perceptions, we first assessed dimensions of importance, frequency, normalcy, and intentions regarding sustainable eating in a group of students (N = 193) within a university cafeteria. Subsequently, we exposed a different group of students (N = 175) with a pluralistic ignorance intervention via a flyer with the aim of correcting potential misperceptions about the social eating norm. While the intervention proved successful in alleviating pluralistic ignorance across three out of four dimensions, it did not increase sustainable food choices. These findings are discussed with a focus on the potential for further development of interventions addressing pluralistic ignorance within the food environment.